Representações sociais sobre o campo de professores egressos do curso de licenciatura em Educação do Campo FAE-UFMG - Naiane Dias Nunes (2019)
The purpose of this research was to study the Social Representations about the field of teachers who graduated from the FAE-UFMG Field Education Course. These implications were understood in the life trajectory of each one of the subjects, going through the context in which they live and with regard to the performance in the rural schools. It is considered that the Social Representations on the field of teachers graduates of the course of Degree in Education of the Field, imply directly in the action of the teachers. It is noted that the subject can have a peasant identity built historically in the struggle, from the action built in its environment, beyond the physical space called territory, as long as its social representations are intertwined with reality / experience, constructed from the individual and collective relationships. In view of this situation, we sought to identify the Social Representations about the field of graduates who are teaching. The methodological approach of this research used a qualitative approach, for which both semi-structured questionnaires were applied and five narrative interviews were carried out in order to understand the implications of the Social Representations on the field of teachers graduating from the FAE-UFMG Field Degree course. For the development of this research, it was necessary to construct a methodological roadmap organized in three stages: bibliographic review, data collection and data analysis. The analyzes indicate that the teachers who are graduates of the course have a look at the students based on the reality experienced by the student and the reality of which the school is inserted, besides presenting a desire of the teachers to do a differentiated work. However, it can be seen that teachers who work alone in a school, find it difficult to carry out work focused on the context of Field Education. The Social Representations of these teachers show that the way in which they are inserted in the field (place that is lived, that takes place and that constitutes itself as subject) implies directly in the way of seeing and understanding its students besides influencing them in the execution of their classes, leading to a concern to work with them on the reality that they live, their territories, their identities.